The relationship between family communication and peer interaction with juvenile delinquency - Veli Safriani; Setiawati Setiawati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Juvenile delinquency remains a concerning social issue in Teluk Merbau Village, manifested in behaviors such as fighting, bullying, smoking, and substance use among adolescents. This study aims to examine the relationship between persuasive family communication and juvenile delinquency, the relationship between peer social interaction and juvenile delinquency, and the simultaneous association of both variables with juvenile delinquency. The research employed a quantitative correlational design involving 56 adolescents aged 10–19 years selected from a population of 186 adolescents using area cluster random sampling across three hamlets. Data were collected through structured questionnaires measuring persuasive family communication, peer social interaction, and juvenile delinquency, which were tested for validity and reliability. The results indicate that persuasive family communication is negatively associated with juvenile delinquency, while negative peer social interaction is positively associated with delinquent behavior. Simultaneously, both variables show a significant relationship with juvenile delinquency, explaining a substantial proportion of behavioral variation. These findings suggest that strengthening family communication and fostering positive peer environments are important considerations in adolescent delinquency prevention efforts.